Faktor Yang Mempengaruhi Kualitas Audit Dengan Etika Profesi Sebagai Variabel Moderating - Atta Putra Harjanto; Kiswanto Kiswanto; Nony Rahmawati; Sri Harjanto (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Auditing is one of the fields in accounting. The public accounting profession has an important role in auditing financial reports in an organization and is a profession trusted by the public. From the public accounting profession, the public expects a free and impartial assessment of the information presented by management in financial reports (Mulyadi and Puradireja, 1998). Harjanto (2014) explains that good audit quality can in principle be achieved if auditors apply audit standards and principles, act freely without taking sides, comply with the law and adhere to the professional code of ethics. This research analyzes factors that influence audit quality. The purpose of this research is to test how much audit quality is produced by auditors. The analysis technique uses MRA analysis with a sample of Semarang City KAP auditors.